Case Report: Management of multiple brown tumors after kidney transplantation - Sun, Qingyi; Bai, Yafei; Chen, Ruman; Li, Hong (Frontiers in Endocrinology, 2025)
Brown tumor is usually caused by primary or secondary hyperparathyroidism but is exceptionally rare after kidney transplantation. Their rarity and atypical pathological features make diagnosis and treatment particularly challenging. We present a case of a 38-year-old woman with multiple brown tumors secondary to persistent hyperparathyroidism following kidney transplantation. The patient was initially admitted to the orthopedic department for left shoulder dislocation and lytic lesions in the left humerus and was diagnosed with a giant cell tumor of bone. Further investigations revealed elevated parathyroid hormone (PTH) levels and multiple lytic bone lesions throughout the skeleton. Based on these findings, the patient was ultimately diagnosed with multiple brown tumors. As a result, the patient underwent total parathyroidectomy and autotransplantation of parathyroid tissue. Follow-up evaluations showed decreased PTH levels and alkaline phosphatase levels, with improvement in skeletal changes. This case report shares the experience and lessons in managing hyperparathyroidism, both before and after kidney transplantation, emphasizing the importance of clinicians’ awareness of the disease and multidisciplinary collaborative management.